2017
DOI: 10.1037/dev0000272
|View full text |Cite
|
Sign up to set email alerts
|

A potential psychological mechanism linking disaster-related prenatal maternal stress with child cognitive and motor development at 16 months: The QF2011 Queensland Flood Study.

Abstract: Fetal exposure to prenatal maternal stress can have lifelong consequences, with different types of maternal stress associated with different areas of child development. Fewer studies have focused on motor skills, even though they are strongly predictive of later development across a range of domains. Research on mechanisms of transmission has identified biological cascades of stress reactions, yet links between psychological stress reactions are rarely studied. This study investigates the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 73 publications
5
51
0
Order By: Relevance
“…This timing effect may be due to the effects of PNMS on the fetal cerebellum, which develops in the third trimester and has been implicated in problems involving social and interpersonal skills such as autism (Brambilla et al., ). This result is consistent with Project Ice Storm's finding of third trimester vulnerability for motor skills at age 5 years, and our own replication of this finding in QF2011 using the ASQ motor scales (Simcock et al., ) and the Bayley motor score (Moss et al., in revision) in infancy. The association between early motor skills and social behavior has been increasingly recognized in the literature (Campos et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…This timing effect may be due to the effects of PNMS on the fetal cerebellum, which develops in the third trimester and has been implicated in problems involving social and interpersonal skills such as autism (Brambilla et al., ). This result is consistent with Project Ice Storm's finding of third trimester vulnerability for motor skills at age 5 years, and our own replication of this finding in QF2011 using the ASQ motor scales (Simcock et al., ) and the Bayley motor score (Moss et al., in revision) in infancy. The association between early motor skills and social behavior has been increasingly recognized in the literature (Campos et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…In the second ( N = 145), there was a near-significant interaction between maternal negative cognitive appraisal of flood-related stress and child sex predicting 16-month gross motor skills. Negative cognitive appraisal of the disaster was associated with poorer motor development among girls but not boys [66]. Bandoli et al examined effects of prenatal alcohol exposure and maternal depression on child psychomotor development at 6 and 12 months of age ( N  = 344).…”
Section: Resultsmentioning
confidence: 99%
“…Simcock et al ( N  = 115) found a sex interaction in the association between disaster-related PNMS and child problem solving at age 6 months, with girls having poorer problem solving than boys at high levels of prenatal stress [48]. In contrast, Moss et al ( N  = 145) found no evidence of sex dependence in the association between PNMS and adolescent cognitive development [66]. In the final paper from this group ( N  = 130), there was a sex-specific effect whereby PNMS was associated with poorer theory of mind in 30-month-old girls but not boys [67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results to date suggest that children exposed to the Queensland floods prenatally demonstrate alterations in development across a range of domains (Austin et al., ; Moss et al., ; Simcock, Laplante, et al., ). Regarding behavioral development, mothers reporting greater flood‐related objective hardship (e.g., extent of property damage), and subjective stress (peritraumatic, posttraumatic, and cognitive reactions) were more likely to describe their 6‐month‐old infants as exhibiting more difficult aspects of temperament, with the specific impacts dependent on infant sex and timing of exposure (Simcock, Elgbeili, et al., ).…”
Section: Natural Disasters As “Natural Experiments”mentioning
confidence: 99%